Diagnóstico ambiental de águas residuárias de empreendimentos da lavagem de veículos em Mossoró/RN - Queiroz, Rosana Nogueira Fernandes de (Universidade Federal Rural do Semi-Árido, 2014)
It is estimated, that is being produced every month in the city of Mossoró, 6096.55 m3 of wastewater from vehicle washing possibly contaminated. In this context, this study aimed to conduct an environmental diagnosis of the wastewater of washing enterprises for vehicles in Mossoró, RN. It was divided into two phases: the first, was conducted the survey city is of the car wash , and identified 34 businesses under the consultancy SEBRAE, within this field sampling were selected, at random, 13 enterprises, applied a questionnaire directed to owners with questions pertaining to the productive process, the source and destination of the water used; in the second stage was held the physico-chemical characterization of wastewater from three of the 13 companies surveyed in the previous step. The parameters analyzed in characterization were: oils and grease, BOD, COD, OD, ST, TSS, turbidity, total Nitrogen, P-total, temperature, Turbidity and pH. The results demonstrate that the wastewater from washing vehicles feature high concentrations of organic matter, oils and greases, turbidity and solid, which are in disagreement with specific environmental legislation. The evaluation demonstrated that although companies performed a primary treatment Water Separators and Oil (SAO), the effluent are not fit to be released into water bodies; It was found that the legal adequacy of companies Lava Jato regarding the treatment of effluents occurs only structurally. The owners are not appropriate of methods and of control standards established by current legislation for effluent discharge
Environmental diagnosis of wastewater car wash developments in Mossoró / RN
Keywords: Effluent; Car Wash; Contamination; Environmental Licensing; Efluente; Lava Jato; Contaminação; Licenciamento Ambiental; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO